PERAN PESANTREN DALAM MENGEMBANGKAN KEWIRAUSAHAANDI KALANGAN SANTRI PONDOK PESANTREN DARUL IHSAN SALOHE - Suriyati; Jamaluddin; Nur, Makmur Jaya; Kahar; Mustamir; Suriyati, Suriyati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Islamic boarding schools (pesantren) are educational institutions that provide religious knowledge to their students. However, apart from that, Islamic boarding schools have a significant contribution to the survival of their alumni. The purpose of this study is to examine the role of Islamic boarding schools in developing entrepreneurship among students at the Darul Ihsan Salohe Islamic Boarding School. In this study, the method used is a qualitative method that involves several data collection techniques, namely interviews, observation, and documentation. To analyze the data, the researcher used several steps, namely data reduction: data is collected and processed to reduce its complexity. Data presentation: The reduced data is presented in a form that is easy to understand and then conclusions are drawn. The results of this study found that the Darul Ihsan Salohe Islamic Boarding School facilitates its students to become entrepreneurs to earn their own income. This is very useful for students because they can earn money from these businesses without burdening their parents. In addition, the economy at the Islamic Boarding School can be improved by the existence of this business unit.